Farber`s Disease: A Case Report - Erfan, Muhammad; Haque, Anwar Ul; Ahmed, Syed Afaq (International Journal of Pathology, 2018)
Background: Farber’s disease also known as disseminated lipogranulomatosis is a very rare disorder of lipid metabolism inherited in autosomal recessive pattern. It is primarily a childhood disorder with defect in ceramide degradation due to deficiency of acid ceramidase within the lysosomes. Clinical features include joint pain and swelling, subcutaneous nodules along with a hoarse voice. In the absence of typical features diagnosis is made either by, measurement of acid ceramidase activity within the cultured skin fibroblasts, white blood cells, amniocytes or by documenting typical histopathological findings on skin/ subcutaneous tissue biopsy. Stem cell transplantation has an important role in treatment of patients who present without any central nervous system findings.Case presentation: We present a case of 2 years old boy diagnosed as juvenile idiopathic arthritis. Detailed history and examination pointed out a possibility of Farber’s disease. Histopathology of a skin nodule confirmed the diagnosis.Conclusion : Farber’s disease being a very rare entity can often be misdiagnosed as juvenile idiopathic arthritis due to many similarities between the two at the time of presentation. This is the second recorded case of Farber’s disease in Pakistan.